TERNATE MALAY CODE MIXING IN ENGLISH TEACHING LEARNING PROCESS AT SMA NEGERI 2 KOTA TERNATE - Suratmin S. Hi. Mahmud; Anwar Ismail; Ali Ajam (Universitas Khairun, 2023)
The objective of this research was to determine the types of Ternate Malay code mixing used by teachers and the reasons for its use in SMA Negeri 2 kota Ternate. This research use a descriptive qualitative method using a descriptive approach. The research subjects consisted of English teachers in grades X and XI. The results of this study indicated that teachers used three types of code mixing, namely inner code mixing, outer code mixing, and hybrid code mixing. The it was also found that three reasons for using code mixing, include the teacher's desire to explain and translate the material, the teacher lacks English vocabulary and it has become a habits.